Assistance in the process of grouping students based on basic literacy and numeracy skills in Karang Sidemen Village - Itsna Oktaviyanti; Lalu Hamdian Affandi; Mohammad Archi Maulyda; Awal Nur Kholifatur Rosyidah; Muhammad Erfan; Iwan Hamdani (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
This community service aims to provide assistance to the process of grouping students based on basic literacy and numeracy skills for teachers in accordance with the “Semua Anak Cerdas” approach in Karang Sidemen Village, North Batukliang District, Central Lombok Regency. Mentoring activities were carried out 1 to 2 times with the target schools for mentoring, among others, SDN Karang Sidemen, SDN Persil, SDN Rangkep, SDN Repuk Sintung Barat, SDN Senurus, and MI NW Nurul Hidayah. Mentoring activities are centred on two focus activities, namely: (1) Grouping students based on basic literacy and numeracy skills; (2) Identifying the number of students who have learning difficulties. Each school is assisted by their respective regional facilitators (FASDA). From this community service, we obtained that students who have good literacy skills are more than those who have numeracy skills, the number of students who experience functional learning difficulties is relatively not different, mentoring activities are running well and in accordance with the expectations of the implementing team, the obstacles encountered are related to mastery of literacy and numeracy concepts, facilities and infrastructure and conditions of students at the time of grouping. The results of the mentoring activity showed that the students' ability in literacy and numeracy was increasing. In addition, because they are in groups with students who have the same ability, students become more confident in class.